2012
DOI: 10.4161/cc.20893
|View full text |Cite
|
Sign up to set email alerts
|

Lin28 regulates HER2 and promotes malignancy through multiple mechanisms

Abstract: The RNA binding protein Lin28 and its paralog Lin28B are associated with advanced human malignancies. Blocking the biogenesis of let-7 miRNA, a tumor suppressor, by Lin28/Lin28B has been thought to underlie their roles in cancer. Here we report that the mRNA for the human epidermal growth factor receptor 2 (HER2), a HER-family receptor tyrosine kinase known to play a critical role in cell proliferation and survival and also a major therapeutic target in breast cancer, is among several targets of Lin28 regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…The expressions of both LIN28 and ENAH have been independently shown to promote malignancy of HER2 breast cancers, but the molecular mechanisms underlying these effects have not been linked (28,46,61). Our study provides evidence suggesting that LIN28 modulates the splicing and expression of human ENAH isoforms that are critical for HER2 signaling in breast cancer cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The expressions of both LIN28 and ENAH have been independently shown to promote malignancy of HER2 breast cancers, but the molecular mechanisms underlying these effects have not been linked (28,46,61). Our study provides evidence suggesting that LIN28 modulates the splicing and expression of human ENAH isoforms that are critical for HER2 signaling in breast cancer cells.…”
Section: Discussionmentioning
confidence: 54%
“…LIN28 is expressed in breast cancer tumors, and recent studies have shown that LIN28 is a powerful predictor of poor prognoses and patient clinical outcomes (8,28,29). With this in mind, we were interested in identifying novel LIN28 mRNA targets that could provide insights into the function of LIN28 in breast cancer.…”
mentioning
confidence: 99%
“…It is now evident that Lin28a is an important oncogene in tumorigenesis (Tu et al 2015) and an emerging maker of cancer stem cells (Ma et al 2014). For example, prolonged expression of Lin28a in primitive mesenchymal kidney cells resulted in increased cell proliferation and Wilms' tumor formation (Feng et al 2012), which strongly suggests that Lin28a-mediated regulation of miRNA production can transcend the niche of undifferentiated cells and affect other miRNAs that are important for proper developmental timing. Thus, studying the systems where Lin28a is overexpressed is of utmost importance to understand its various roles in cancer biology.…”
Section: Discussionmentioning
confidence: 99%
“…3 In particular, overexpression of ErbB2 has been demonstrated to promote breast cancer invasion and metastasis and to correlate with poor patient survival. [4][5][6][7] However, ErbB2 is also overexpressed in non-invasive mammary ductal carcinomas in situ (DCIS). 8 Indeed, ErbB2 amplification or overexpression seems to be crucial but not sufficient for the transition from in situ to invasive cancer, and additional hits are required for the progression of ErbB2-positive tumors.…”
Section: Introductionmentioning
confidence: 99%